A process for new program development. Issue 10 (June 2018) - Crowley, Timothy R.
Abstract : One common challenge for many nonprofit institutions is developing new programs in a timely manner. Focus, program launch time, and insufficient project management are usually the constraining factors in this complex process. This article proposes a solution to these constraining factors that attempts to borrow from the corporate world to integrate a solution into contemporary institutions that incorporate shared governance and traditional college/departmental hierarchical structures.